Efficient and Reliable Data Dissemination Approaches for VANET - Sharma, Mamillapally Raghavender (International Journal of Computer Sciences and Engineering, 2025)
VANET Technology is the tremendously increasing day to day and a prominent research technology in the area of vehicular nodes which provides with concrete and real applications. Prominent development of applications and inherent characteristics such as frequent disconnection of network, rapid dynamic topology, and predictable mobility have made data dissemination technique inside VANET system as a crucial challenging task in the significant area of wireless sensor networks. Many of VANET applications require real-time communication with high reliability. Data dissemination is the base for whole network and it is a mechanism of spreading the data or information over dispersed networks. Data dissemination is intended to use the resources of a network in an optimal way to provide the needs to end users in dedicated network environment. To initiate efficient data dissemination technique in VANET system we have to consider both data forwarding node and not participated nodes in that data dissemination. So, data dissemination protocol should be designed exclusively so that achieves dissemination of data to end point without affecting data in dense and sparse network of VANET system. In this paper, we discuss the data dissemination protocols history thoroughly. The main objective of this paper is to provide fundamental concepts of data dissemination in VANET system environment